TINJAUAN YURIDIS TERHADAP PENYALAHGUNAAN NARKOTIKA - Pinem, Aldi Elkana Pinem; I Dewa Ayu Widyani; Edward ML Panjaitan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
The imposition of imprisonment for abusers for themselves becomes increasingly inappropriate and not useful when the capacity of prisons or state detention centers becomes overcapacity because the occupants are dominated by narcotics abusers. Therefore, it is necessary to review the imposition of criminal sanctions on narcotics abusers for themselves. This research is a normative research, and is descriptive analytical in nature which describes and analyzes a phenomenon related to the Criminal Imposition of Narcotics Users for Themselves (Study of the Decision of the Jakarta Pusat District Court No. 585/Pid.Sus /2021/PN.Jkt.Pst and District Court Decisions Medan No. 329/Pid.Sus/2021/PN.Mdn). The results of the study, criminal sanctions for narcotics abusers for themselves are subject to imprisonment. However, if the actions of narcotics abusers themselves meet the provisions of SEMA No. 4 of 2010, drug abusers for themselves "can" be rehabilitated. Judge's consideration in making decisions for the perpetrators of criminal acts of narcotics abusers for themselves in the Decision of the Jakarta Pusat District Court No.585/Pid.Sus/2021/PN.Jkt.Pst and Decision of Medan District Court No.329/Pid.Sus/202 / PN.Mdn is not enough just to refer to the construction of the norms listed in Article 127 of Law No. 35 of 2009 concerning Narcotics, but also must pay attention to related rules, for example SEMA No. 4 of 2010. This is because the article does not contain clear criteria related to narcotics abusers for themselves where such considerations are in line with the legal system both legal structure, legal substance and legal culture. Position of rehabilitation in Law No. 35 of 2009 concerning Narcotics is "can" is not "mandatory".